A Prospective Open-Label Trial of Memantine Hydrochloride for the Treatment of Social Deficits in Intellectually Capable Adults With Autism Spectrum Disorder. Issue 3 (June 2016) - Joshi, Gagan; Wozniak, Janet; Faraone, Stephen V.; Fried, Ronna; Chan, James; Furtak, Stephannie; Grimsley, Emily; Conroy, Kristina; Kilcullen, J. Ryan; Woodworth, K. Yvonne; Biederman, Joseph
Abstract : Abstract: This prospective 12-week open-label trial evaluates the tolerability and efficacy of memantine hydrochloride for the treatment of core social and cognitive deficits in adults with high-functioning autism spectrum disorder (ASD). Measures for assessment of therapeutic response included the Social Responsiveness Scale-Adult Research Version (SRS-A), disorder-specific Clinical Global Impression scales, Behavior Rating Inventory of Executive Functioning–Adult Self-Report, Diagnostic Analysis of Nonverbal Accuracy Scale, and Cambridge Neuropsychological Test Automated Battery. Eighteen adults (mean age, 28 ± 9.5 years) with high-functioning ASD (SRS-A raw score, 99 ± 17) were treated with memantine (mean dose, 19.7 ± 1.2 mg/d; range, 15–20 mg), and 17 (94%) completed the trial. Treatment with memantine was associated with significant reduction on informant-rated (SRS-A, −28 ± 25; P < 0.001) and clinician-rated (Clinical Global Impression-Improvement subscale ⩽2, 83%) measures of autism severity. In addition, memantine treatment was associated with significant improvement in ADHD and anxiety symptom severity. Significant improvement was noted in nonverbal communication on the Diagnostic Analysis of Nonverbal Accuracy Scale test and in executive function per self-report (Behavior Rating Inventory of Executive Functioning–Adult Self-Report Global Executive Composite, −6 ± 8.8; P < 0.015) and neuropsychological assessments (Cambridge Neuropsychological Test Automated Battery). Memantine treatment was generally well tolerated and was not associated with any serious adverse events. Treatment with memantine appears to be beneficial for the treatment of ASD and associated psychopathology and cognitive dysfunction in intellectually capable adults. Future placebo-controlled trials are warranted.